Long‐term risk of recurrent venous thromboembolism after a first contraceptive‐related event: Data from REVERSE cohort study. (21st April 2021) - Aziz, David; Skeith, Leslie; Rodger, Marc A.; Sabri, Elham; Righini, Marc; Kovacs, Michael J.; Carrier, Marc; Kahn, Susan R.; Wells, Philip S.; Anderson, David R.; Chagnon, Isabelle; Solymoss, Susan; et al.
Abstract: Introduction: The risk of recurrent venous thromboembolism (VTE) after combined oral contraceptive (COC) use is variably reported. We assessed the long‐term risk of recurrent VTE in women on COC at the time of a first VTE, in comparison to women without COC use. Our secondary aim assessed the impact of COC use on the recurrent VTE risk in high‐risk and low‐risk hyperpigmentation, edema, or redness in either leg; D‐dimer level ≥250 μg/L; obesity with body mass index ≥30; or older age, ≥65 years (HERDOO2) subgroups. Methods: The REVERSE cohort study derived the HERDOO2 clinical decision rule to predict recurrent VTE in patients who discontinued anticoagulation after 5–7 months for a first unprovoked VTE. Incidence rates of recurrent VTE among women with and without COC exposure were calculated as the number of recurrent VTE over the number of person‐years of follow‐up, and Cox proportional hazards model was used to compare risks between groups. Results: The risk of recurrent VTE among COC users was 1.1% (95% confidence interval [CI] 0.3–2.9) per patient‐year as compared with 3.2% per patient‐year (95% CI 2.4–4.3) among nonusers (hazard ratio 0.37; 95% CI 0.1–1.0). Women who were COC users and high risk by HERDOO2 score had a recurrence rate of 3.5% (95% CI 0.4–12.5) compared with 6.1% (95% CI 4.3–8.5) among women who were non‐COC users and at high risk by HERDOO2 score (HR 0.6, 95% CI 0.1–2.5). Conclusions: Women who were COC users at the time of an otherwise unprovoked VTE event had a lower VTE recurrence rate during long‐term follow‐up, compared with nonusers. The use of HERDOO2 rule may help identify higher risk women with COC use.